Emotional Maturity of Senior Secondary School Students in District Pulwama of Jammu and Kashmir - Talie , Ashaq Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
The present study investigated the emotional maturity of senior secondary school students in Pulwama district of Jammu and Kashmir. The study included 300 students in class 12th, with equal representation of boys (150) and girls (150), in the Pulwama district. The students were chosen using a simple random sampling technique, and the 12 schools were chosen using a stratified random sampling technique. The Emotional Maturity Scale (M. Bhargava and Y. Singh 1990) is used to collect data using the descriptive survey method. According to the findings of the study, there are significant differences in emotional maturity between government and private senior secondary school students. However, there is no significant difference between male and female senior secondary school students in Pulwama district, according to the report.